UNDERSTANDING THE CONSEQUENCES OF TEACHERS’ AGGRESSIVE BEHAVIOR ON PUPILS’ ACADEMIC MOTIVATION IN ANAMBRA EAST L.G.A - K, Cherry; Igwe, A (Academic Journal of Psychology and Education (AJPE), 2022)
This study investigates the impact of teachers’ aggressive behavior on pupils’ academic motivation in Anambra East Local Government Area, Anambra State, Nigeria. The study was carried out among 120 teachers (70 females and 50 males) teaching in public schools in the area. The research instrument used for data collection was the “Teachers Aggressive Behavior Survey (TABS)” developed by the researchers. The findings of the study revealed that teachers’ aggressive behavior discourages pupils from actively participating in classroom academic activities, such as calling learners names, yelling, threatening, hitting, and slapping. Additionally, the study showed that teachers’ aggressive behavior leads to learners dorging classroom academic activities, reducing their confidence and interest during classroom instruction. The study recommends that school administrators should sensitize teachers on the influence of aggressive behavior on pupils’ academic motivation. This study is paramount as the aggressive behavior of teachers is known to affect pupils, thereby hampering their academic development